2022
DOI: 10.1149/1945-7111/ac9ee0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Heat Removal and H2O Retention Capability of Passive Air-Cooled Polymer Electrolyte Membrane Fuel Cells by Tailoring Cathode Flow-Field Design

Abstract: This paper reports novel cathode flow-field designs for passive typed air-cooled polymer electrolyte membrane fuel cells (PEMFCs) to help alleviate electrolyte dehydration and performance degradation issues under excess dry air supply conditions. The proposed flow-field designs include 7 three-dimensional (3-D) patterned designs in addition to a parallel channel configuration equipped with rectangular baffles to control the airflow for more efficient heat removal. The designs were evaluated numerically using 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…shows the temperature distribution at the outer surface of the GDL for the experimental and the current simulations. According to the figure it can be concluded that the temperature distribution along the fuel cell for the current simulation has a good agreement with the experimental simulation conducted by Kisung Lim[29].…”
supporting
confidence: 79%
“…shows the temperature distribution at the outer surface of the GDL for the experimental and the current simulations. According to the figure it can be concluded that the temperature distribution along the fuel cell for the current simulation has a good agreement with the experimental simulation conducted by Kisung Lim[29].…”
supporting
confidence: 79%
“…To validate the numerical model, Figure 10 compares the temperature distribution on the outer surface of the GDL from experimental data by Lim et al [29] with current simulations. The temperature distribution along the fuel cell from the simulation agrees well with a difference of less than 5%.…”
Section: Design Validationmentioning
confidence: 99%